The value of hands-on experiments in an upper-division classical mechanics course - Tarr Steven W.; Brunner Joseph S.; Alicea-Muñoz Emily; Goldman Daniel I. (Emergent Scientist)
We share our experience incorporating open-ended experimentation into an upper-division classical mechanics course through project-based learning, including one student’s investigation of a common textbook problem and its unexpected connections to astrophysics. By iterating a computational model and an experimental apparatus, the student participated in inquiry in a way that would not have been possible in a typical classical mechanics course. We advocate the adoption of similar hands-on approaches in the classroom to help upper-division students develop both an understanding of the value of experimentation and an appreciation of the diversity and subtlety of physical phenomena that can emerge in apparently simple systems.